2019
DOI: 10.1007/s40140-019-00351-y
|View full text |Cite
|
Sign up to set email alerts
|

Transversus Abdominis Plane (TAP) and Rectus Sheath Blocks: a Technical Description and Evidence Review

Abstract: Purpose of Review This article aims to review the anatomy relevant to the ultrasound techniques of the transversus abdominis plane (TAP) block and rectus sheath block (RSB). We discuss their analgesic efficacy for various surgical procedures, both as single shot and as a continuous infusion via catheters. Recent Findings RSB provides superior analgesia to local infiltration and has an opioid-sparing effect for umbilical surgery, laparotomy, and laparoscopic surgery. There is no high-quality evidence comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 61 publications
(39 reference statements)
0
22
0
4
Order By: Relevance
“…Transversus abdominis plane blocks involve the deposition of the local anesthetic in the fascial plane between the transversus abdominis and internal oblique muscles. 6 The exact location of the injection is quite important. Posterior TAP injections have been shown to be superior to lateral TAP blocks in terms of 24-hr opioid consumption and pain scores.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Transversus abdominis plane blocks involve the deposition of the local anesthetic in the fascial plane between the transversus abdominis and internal oblique muscles. 6 The exact location of the injection is quite important. Posterior TAP injections have been shown to be superior to lateral TAP blocks in terms of 24-hr opioid consumption and pain scores.…”
mentioning
confidence: 99%
“…The dearth of TAP catheter studies in the obstetric population is not surprising given additional feasibility and safety problems as already mentioned regarding WC. 6 Whether there is any analgesic superiority of TAP catheters to single-shot TAP blocks remains uncertain in the CD population. Nevertheless, a recent study showed no benefit of TAP catheters over single-shot TAP blocks in patients having laparoscopic live-donor nephrectomy.…”
mentioning
confidence: 99%
See 3 more Smart Citations